Inovasi Papan Informasi Penggunaan dan Perawatan APAR dan Hydrant di Lapas Kelas IIA Gunung Sindur - Setiawan, Helmi Budi (Yayasan Daarul Huda Kruengmane, 2024)
A correctional institution is a place to carry out punishment for convicts who have been sentenced. One of the non-natural disasters that occurs quite frequently in correctional institutions is fire. Fire is a disaster that is detrimental to many parties, which can result in significant material losses and potential for death, so it requires attention to the safety of employees and also correctional inmates in the Gunung Sindur Class IIA Special Prison. The aim of community service is to provide solutions related to anticipating fires with APAR and Hydrants in Class IIA Gunung Sindur Prison. The implementation of the method in community guidance practice is using a community best correction method and organizational development or community development where this method is used for cadets to carry out practicum as an effort to help improve the function of the implementation of prisoner guidance both inside and outside the institution. The final result of program implementation is that the Gunung Sindur Class IIA Special Correctional Institution already has adequate facilities, means and infrastructure both in the areas of coaching, security and service. This is no exception to tools that can deal with fire disasters such as light fire extinguishers (APAR) and hydrants. The existence of these tools must of course also be accompanied by knowledge about how to use and care for these tools. This is an important thing because if something undesirable happens, the tool can function as it should and both officers and inmates in the block can operate it so that a fire disaster does not cause significant losses.